White matter hyperintensity mediating gait disorders in iNPH patients via neurofilament light chain - Yang, Lu; Yang, Fuxia; Deng, Yao; Yan, Aijuan; Wei, Wenshi; Fang, Xuhao (Frontiers in Aging Neuroscience, 2023)
Purpose: This study aimed to analyse the differences in regional white matter high signal volume and cerebrospinal fluid biomarker levels between idiopathic normal pressure hydrocephalus (iNPH) patients with or without gait disorder. Methods: Forty-eight iNPH patients undergoing bypass surgery and 20 normal senile individuals were included. The LST toolkit was used to segment all MRI fluid attenuation inversion images and quantify the high white matter signal volume in each brain region. Cerebrospinal fluid was collected from all individuals and measured for concentrations of Aβ, t-tau, p-tau, and NfL. Patients with iNPH were followed up for 1 year and divided categorised into a gait disorder improvement group and no improvement group according to the 3m round-trip test time parameter improvement by more than 10%. Results: We found that WMH in all areas of iNPH patients was higher than that in the control group. CSF levels of Aβ, t-tau, and p-tau were lower than those in the control group, while NfL levels were higher than those in the control group. The gait (+) group NfL level was higher than that in gait (-), and there were no statistical differences in Aβ, t-tau, and p-tau levels. The gait (+) group of frontal and parietal lobe WMH volume PVH above the gait (-) group.The mediating effect model analysis showed that PVH might affect the gait disorder of iNPH patients through NfL. A 1-year follow-up of the patients after the bypass surgery found that 24 of the 35 patients in the gait (+) group had improvements, while 11 had no significant improvements. The comparison of CSF marker levels between the two groups showed that the CSF NfL level in the improved group was lower than that in the non-improved group. The WMH volume and PVH in the frontal-parietal lobe of the improved group were lower than those of the non-improved group. Conclusion: iNPH patients have more serious frontoparietal and periventricular white matter lesions, and WMH volume in the frontoparietal may mediate the occurrence of gait disorder in iNPH patients through the increase of NfL level.